Effects of picking methods on the berry production of bilberry ( Vaccinium myrtillus ), lingonberry ( V. vitis-idaea ) and crowberry ( Empetrum nigrum ssp. hermaphroditum ) in Northern Finland - Manninen, Outi; Peltola, Rainer (Silva Fennica, 2013)
The effect of commercial wild berry picking on berry yields is under a strong public debate in Finland. Especially high concern has been arisen over damages caused by metal rakes used in commercial picking to subsequent berry production. We studied the berry production of bilberry ( L.), lingonberry ( L.) and crowberry ( ssp. (Hagerup) Böcher) after picking the berries by 1) plastic hand rake, 2) long-handed metal rake and 3) powerful picking by long-handed metal rake, in northern Finland during 2010â2012. In the powerful long-handed metal rake treatment the aboveground vegetation was raked twice to the moss layer after berry picking. Biomass, which was removed from the vegetation by rakes was collected and used as a measure of the damage. We assumed that picking by plastic hand rake would result in lowest, long-handed metal rake intermediate and powerful picking by long-handed metal rake highest biomass loss from vegetation. The amount of biomass loss should in turn be reversely reflected into berry production. However, only the powerful picking by long-handed metal rake removed higher amount of biomass than other picking methods in bilberry and lingonberry. In crowberry, the amount of biomass removed by rakes increased from treatment to treatment. Contrary to our assumption, berry production of bilberry, lingonberry and crowberry was not affected by the damage caused by any of the picking method. We conclude that long-handed metal rake used in commercial picking is comparable to hand rake in terms of berry production.Vaccinium myrtillusV. vitis-idaeaE. nigrumhermaphroditum